DESIGNING BEAUTY EDUCATION FOR EMPATHY: CURRICULUM BLUEPRINT FOR EMOTIONALLY INTELLIGENT NAIL TECHNICIANS - Shtanhei, Olha (Global Prosperity, 2025)
The article focuses on the development of a training program for nail service professionals, emphasizing emotional intelligence and empathy as essential components of professional practice in the beauty industry. The aim of the article is to justify the necessity of including empathy as a core element in the professional training of nail technicians and to design an integrated curriculum that combines technical, emotional, and communication competencies with a strong emphasis on emotional intelligence in the educational process. The study employed general scientific methods of cognition: analysis and synthesis; induction and deduction; modeling; systematization; comparative pedagogical method; and generalization of scientific sources. The research findings show that current educational training for nail service specialists is based on a combination of fundamental scientific disciplines (dermatology, material chemistry, hygiene), practical skills (classic and machine manicure, artistic design), as well as entrepreneurship elements. At the same time, a number of issues were identified, with the most significant being the lack of standardized pedagogical training for instructors and insufficient adaptation of educational content to industry innovations, which complicates the integration of socio-psychological components such as empathy. The study demonstrates that empathy plays a critical role in effective professional interaction within the beauty service sector, particularly in the work of nail service professionals. It develops on three levels – subjective, interpersonal, and objective – and influences a specialist’s ability to accurately recognize and interpret clients’ emotions, build trusting communication, and enhance satisfaction with the service provided. The proposed curriculum takes these factors into account and includes modules where empathy is integrated through active learning methods: case studies; role-playing; emotionally charged scenario modeling; and reflective practices. Implementing these strategies supports the development of soft skills, including active listening, nonverbal communication, and emotional self-regulation, which are vital components of a professional’s competency. The practical significance of the study lies in the creation of a holistic pedagogical model for training emotionally intelligent specialists capable of delivering client-centered, aesthetically thoughtful, and emotionally comfortable services.